Concise review of recent advances and applications of the electron linear accelerator ELU 4 in scientific and technical fields; Physical Sciences and Technology.; Vol. 11, No. 1-2 - Nakysbekov Zh. Zhassulan; Ismailov D. Daniyar; Bellucci S. Stefano; Tukhfatullin T. A. Timur Ahatovich; Bogdanov O. V. Oleg Viktorovich; Tronin B. Boris; Turmanova K. Kundyz; Suyundykova G. Gulnur; Grichshenko V. Valentina; Pshikov M. Mustakhim; Alzhanova A. Assem (2024, 2024)
Title screen